THE COMPARISON OF SIMPLE MOVING AVERAGE AND DOUBLE EXPONENTIAL SMOOTHING METHODS IN PREDICTING NEW DEBTORS - Agatha Anggraeni Dewi; Darsih Idayani (STMIK Royal, 2023)
Abstract: The realization of credit proposed by customers is one of the essential factors for a bank. Moreover, especially during the Covid-19 pandemic, credit realization shows the business conditions of prospective borrowers, whether they are in good condition or not. So, it is crucial to predict how many new debtors will achieve. In this article, forecasting the number of new debtors uses the Simple Moving Average and Double Exponential Smoothing methods based on actual data on the number of new debtors per month for 2019-2021. Furthermore, the performance of the two methods is compared by comparing the Mean Absolute Deviation and Mean Square Error values. The comparison results conclude that the Simple Moving Average method is better than the Double Exponential Smoothing for predicting the number of new debtors. Keywords: double exponential smoothing; mean absolute deviation; mean square error; simple moving average; forecasting. Abstrak: Realisasi kredit yang diajukan oleh nasabah adalah salah satu faktor yang penting di dunia perbankan. Terlebih disaat adanya pandemi Covid-19, realisasi kredit memperlihatkan kondisi usaha para calon debitur, apakah dalam keadaan baik atau tidak. Sehingga penting untuk memprediksi berapa capaian jumlah debitur baru. Dalam artikel ini dilakukan peramalan jumlah debitur baru dengan metode Simple Moving Average dan Double Exponential Smoothing berdasarkan data aktual jumlah debitur baru per bulan tahun 2019-2021. Selanjutnya, dilakukan perbandingan performa kedua metode tersebut dengan cara membandingkan nilai dari Mean Absolute Deviation dan Mean Square Error. Hasil perbandingan yang diperoleh mengarah pada sebuah kesimpulan, yaitu metode Simple Moving Average lebih baik daripada Double Exponential Smoothing untuk meramalkan jumlah debitur baru Kata kunci: double exponential smoothing; mean absolute deviation; mean square error; simple moving average; peramalan.